2021
DOI: 10.3390/genes12121924
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Selective Signatures Reveal Candidate Genes Associated with Hair Follicle Development and Wool Shedding in Sheep

Abstract: Hair follicle development and wool shedding in sheep are poorly understood. This study investigated the population structures and genetic differences between sheep with different wool types to identify candidate genes related to these traits. We used Illumina ovine SNP 50K chip genotyping data of 795 sheep populations comprising 27 breeds with two wool types, measuring the population differentiation index (Fst), nucleotide diversity (θπ ratio), and extended haplotype homozygosity among populations (XP-EHH) to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 49 publications
(60 reference statements)
0
6
0
Order By: Relevance
“…Gene expression is regulated by noncoding RNAs, including miRNAs. MiRNAs, which are endogenously expressed in mammals [32][33][34], are 18-22-nucleotide (nt), small noncoding RNAs that are evolutionarily conserved and negatively regulate the expression of target mRNAs mainly by repressing translation or, in some cases, by cleaving mRNA transcripts [35,36]. miRNAs play a key role in many biological processes by regulating gene expression at the posttranscriptional level.…”
Section: Introductionmentioning
confidence: 99%
“…Gene expression is regulated by noncoding RNAs, including miRNAs. MiRNAs, which are endogenously expressed in mammals [32][33][34], are 18-22-nucleotide (nt), small noncoding RNAs that are evolutionarily conserved and negatively regulate the expression of target mRNAs mainly by repressing translation or, in some cases, by cleaving mRNA transcripts [35,36]. miRNAs play a key role in many biological processes by regulating gene expression at the posttranscriptional level.…”
Section: Introductionmentioning
confidence: 99%
“…Knockdown of CD80 in mouse has been shown to result in a high susceptibility to infection, leading to disease phenotypes similar to those observed in human alopecia areata [25]. PRX , involving in cell proliferation, plays an important role in HF development and wool shedding [26]. The alterations in the expression of these genes in the study suggest that HFSCARC is an important player in the HF cycle.…”
Section: Discussionmentioning
confidence: 66%
“…Jin et al [23] identified SNPs with the top 5% of the XP-EHH values using SNP microarray genotyping data on 53 goats from three breeds. Lei et al [54] identified SNPs with XP-EHH <−2 using available SNP microarray genotyping data on 795 sheep from 27 breeds divided into two groups (fine-wool sheep and hair sheep). Zhang et al [55] identified SNPs with the top 1% of the XP-EHH values using sequencing data on 47 sheep from three breeds.…”
Section: Methods 3 Selection Signaturesmentioning
confidence: 99%